E – Commerce Penjualan Gitar Berbasis Web di Cahaya Guitar dengan Codeigneter dan MySQL - Melianingsih, Nuning; Anggraini, Yunita Kusuma (Jurnal Informa : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
The use of information technology in a business activity is quite important. It is so important that almost every company uses an online business service system, one of which is Web E-Commerce. Cahaya Guitar is a business making guitars that are made directly from starting materials to finishing, which was founded in 2014 and is located in Mancasan Village, Baki District, Sukoharjo Regency. The online sales system used at Cahaya Guitar still uses Facebook and Instagram facilities so sales are still minimal and not very widespread. So it requires other media to make sales easier and can go global. Apart from that, Cahaya Guitar records sales transaction data manually, and is not very structured so that errors often occur in making reports.The research objective is to design a Web-Based Guitar Sales E-Commerce at Cahaya Guitar with CodeIgneter and MySQL. The research method used is the MDLC (Multimedia Development Life Cycle) method. In this method there are six stages, namely conceptualization, design, material collecting, assembly, testing and distribution. The result of this research is a web-based sales system (e-commerce) at Cahaya Guitar using the PHP and MYSQL programming languages.